2020
DOI: 10.1088/1361-6382/ab7ee4
|View full text |Cite
|
Sign up to set email alerts
|

AdS Robin solitons and their stability

Abstract: We consider the four-dimensional Einstein-Klein-Gordon-AdS system with conformal mass subject to the Robin boundary conditions at infinity. Above a critical value of the Robin parameter, at which the AdS spacetime goes linearly unstable, we prove existence of a family of globally regular static solutions (that we call AdS Robin solitons) and discuss their properties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The question of stability of the solutions with V ′′ (0) < 0 is unclear (compare [36], and there are in fact hints that some solutions with V ′′ (0) < 0 might be stable [9]), but this is irrelevant from the point of view of the question existence of static or stationary solutions, which is our main interest in this work.…”
Section: Static Metricsmentioning
confidence: 99%
“…The question of stability of the solutions with V ′′ (0) < 0 is unclear (compare [36], and there are in fact hints that some solutions with V ′′ (0) < 0 might be stable [9]), but this is irrelevant from the point of view of the question existence of static or stationary solutions, which is our main interest in this work.…”
Section: Static Metricsmentioning
confidence: 99%
“…We will study the spectrum of the scalar field ϕ with conditions (2.2) and (2.3). In [21], it has been shown that the Klein-Gordon equation for spherically symmetric scalar field in the global AdS 4 reduces to equation (2.1) and instability has been found for certain Robin boundary conditions 2 . (See also [17] for the case of semi-infinite 1 Precisely speaking, the boundary condition (2.2) can be rewritten as…”
Section: Spectrummentioning
confidence: 99%
“…In [18][19][20], the effect of the Robin boundary condition on the superradiant instability of rotating and charged black holes in AdS was studied. A nonlinear solitonic solution was also explicitly constructed under the Robin condition as a candidate of the final fate of the instability of the global AdS [21]. In [22], hairy charged black holes and charged boson stars under the Robin conditions were constructed and their phase structure has been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…We will fine-tune and vary Q B in such a way that through eq. (3.43), the resultant φ 0 changes from where f = φ/z [31]. When α is large enough, the boundary condition reduces to β kα 2 that preserves all the asymptotic AdS symmetries [32].…”
Section: Interpolating Near Horizon To Asymptotic Adsmentioning
confidence: 99%